THE PUBLIC ADMINISTRATION SYSTEM OF THE COUNTRIES OF EASTERN EUROPE IN THE FIRST YEARS AFTER ACQUIRING MEMBERSHIP IN THE EUROPEAN UNION - MELNYK, Andriy; IVASHCHENKO, Anton (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This article examines the transformation of public administration systems in Eastern European countries in the first years after their accession to the European Union. After gaining membership in the EU, the countries of the region experienced significant changes in their political, economic and social environments, which had a significant impact on public administration and administrative structures [1]. Key changes are analyzed, such as the adaptation of European governance standards, including ensuring transparency, accountability and efficiency of public institutions, as well as strengthening the rule of law and adherence to the principles of democratic governance. Particular attention is paid to the mechanisms of adaptation of management processes to the EU norms and requirements, which require deep structural reforms. The article also explores the role of European institutions in supporting Eastern European member states in implementing reforms and highlights the challenges faced by these countries in the process of adaptation. The paper examines various aspects of governance, including the modernization of bureaucratic systems, decentralization of power, anti-corruption initiatives, and the introduction of e-government. Using examples from Poland, the Czech Republic, Hungary, and other countries, the paper illustrates positive developments and problematic issues that remain relevant in the context of further integration. The results of the study aim to provide a deeper understanding of the public administration reform processes and identify prospects for further development of integration efforts, which may be useful for scholars, policy makers, managers and other stakeholders working in the field of European integration and public administration. The study examines key aspects of public administration transformation in Eastern European countries after their accession to the EU. The adaptation of state institutions to European standards of transparency and efficiency is analyzed. The mechanisms of support from European institutions in the process of reforms implementation are studied. Particular attention is paid to the challenges and problems faced by countries in the course of adaptation. The results of the study provide valuable recommendations for further development of public administration in the context of European integration.
Keywords: public administration; Eastern Europe; European Union; European integration; political reforms; administrative structures; institutional adaptation